2022
DOI: 10.1002/advs.202104598
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Near‐Infrared Circularly Polarized Light Detection Using 3D Perovskite Embedded with Chiral Plasmonic Nanoparticles

Abstract: Chiral organic ligand-incorporated low-dimensional metal-halide perovskites have received increasing attention for next-generation photodetectors because of the direct detection capability of circularly polarized light (CPL), which overcomes the requirement for subsidiary optical components in conventional CPL photodetectors. However, most chiral perovskites have been based on low-dimensional structures that confine chiroptical responses to the ultraviolet (UV) or short-wavelength visible region and limit phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…16,17 Recently, metal halide perovskites imprinted with chiro-optical properties by chiral organic ligands have added to the desirable optoelectronic properties of perovskite materials for applications in spin-dependent optoelectronic devices, 18 spin-polarized charge transport, 19–21 and circularly polarized light emission 22–24 and detection. 25–27 Moon et al reported the first synthesis of chiro-optically active hybrid organic–inorganic 2D metal halide perovskite thin films in 2017. 28 Since then, a gamut of 2D 19,29–31 and 3D 32–37 chiral perovskites which display a range of interesting chiro-optical and spintronic properties have been synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Recently, metal halide perovskites imprinted with chiro-optical properties by chiral organic ligands have added to the desirable optoelectronic properties of perovskite materials for applications in spin-dependent optoelectronic devices, 18 spin-polarized charge transport, 19–21 and circularly polarized light emission 22–24 and detection. 25–27 Moon et al reported the first synthesis of chiro-optically active hybrid organic–inorganic 2D metal halide perovskite thin films in 2017. 28 Since then, a gamut of 2D 19,29–31 and 3D 32–37 chiral perovskites which display a range of interesting chiro-optical and spintronic properties have been synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…(a) Flexible perovskite photodetector on a flexible substrate and photocurrent mapping of the photosensor matrix exposed to a heart-shaped laser RCPL illumination and LCPL illumination. Reprinted with permission under a Creative Commons CC BY from ref . Copyright 2022 John Wiley and Sons.…”
Section: Applicationsmentioning
confidence: 99%
“…Various plasmonic designs based on Au, Ag, and Al nanoparticles were also proposed for perovskite photodetectors, where one of the highest nanostructure-empowered enhancement of external quantum efficiency as high as 2.5 times was demonstrated in the work . Also, near-infrared circularly polarized light detectors fabricated using chiral Au NPs embedded to Pb–Sn perovskite films exhibited remarkable chirality in the near-infrared region with high anisotropic response, owing to a giant plasmon resonance shift of chiral plasmonic Au NPs, which might be prospective to chiral perovskite optoelectronics. , …”
Section: Halide Perovskitesmentioning
confidence: 99%